Islam and the Abolition of Slavery - Muhammad M. Haque (International Institute of Islamic Thought, 2007)
This book delves into Islam and its connection with slavery in historical and etiological terms by presenting the synthesis in an almost axiomatic manner that “slavery has always been a part and parcel of the basic core and a central tenet of Islam.” The author relies on various scholarly sources, including the Qur’an and the hadiths, with the bulk of information coming from non- Islamic sources. Providing quotes from various scholars (e.g., Lewis, Muir, Berlioux, Hughes, Garrett, Margoliouth, Roberts, and DeJong) (pp. 16-17), Clarence-Smith brings out of a set of synergistic syllogisms on the assumptive plane that the Qur’an failed to eliminate slavery, that removing this practice would shake the faith itself, that the Prophet was totally unaware of the concept of abolition as an idea as well as in practice, and, importantly, that the whole Islamic social structure with its attendant system was based on a type of slavery associated with the organization of the harem. Hence, from the author’s point of view, Islam in essence kept slavery within a massive infrastructure and played a negligible role in its demise. Moreover, the system was abolished mostly due to western effort rather than any purely religious guidelines or impetus. This organized form of slavery included singing girls, concubines, common soldiers from the ranks of war captives as well as non-war captives, cannon fodder, bond maidens, harem guards, and chattel similar to livestock – collectively often reaching into the millions. While there were examples of slaves rising to the position of amir, such instances are exceptions and extremely rare. The author defends his argument’s basic propositions in eleven highly condensed chapters. The first chapter, “Introduction,” basically details his central thesis with supporting arguments, including the intensity of the slave systems as highlighted above. The concluding segment, “Envoi,” outlines the current responsibilities of different religious groups for a greater cooperation and unity toward the process of slavery’s final elimination and apologizing for past misdeeds ...